2018
DOI: 10.1002/ece3.3710
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA variation reveals maternal origins and demographic dynamics of Ethiopian indigenous goats

Abstract: The Horn of Africa forms one of the two main historical entry points of domestics into the continent and Ethiopia is particularly important in this regard. Through the analysis of mitochondrial DNA (mtDNA) d‐loop region in 309 individuals from 13 populations, we reveal the maternal genetic variation and demographic dynamics of Ethiopian indigenous goats. A total of 174 variable sites that generated 231 haplotypes were observed. They defined two haplogroups that were present in all the 13 study populations. Ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 40 publications
21
34
1
Order By: Relevance
“…This study conducted the first assessments of genetic population structure, genetic diversity, phylogenetic status, and the origin of Mongolian goats using the most polymorphic HVI region in mtDNA. This highly polymorphic region (indeed, the complete D-loop) has been routinely used in previous studies that examined genetic diversity, phylogenetic relationships, and especially the maternal origin of most domesticated animals, including goats [14,[33][34][35][36][37]. Similar to previous results [17,38,39], goats from Mongolia investigated in this study showed high mtDNA diversity.…”
Section: Genetic Diversitysupporting
confidence: 79%
See 2 more Smart Citations
“…This study conducted the first assessments of genetic population structure, genetic diversity, phylogenetic status, and the origin of Mongolian goats using the most polymorphic HVI region in mtDNA. This highly polymorphic region (indeed, the complete D-loop) has been routinely used in previous studies that examined genetic diversity, phylogenetic relationships, and especially the maternal origin of most domesticated animals, including goats [14,[33][34][35][36][37]. Similar to previous results [17,38,39], goats from Mongolia investigated in this study showed high mtDNA diversity.…”
Section: Genetic Diversitysupporting
confidence: 79%
“…mismatch distribution pattern was multimodal for all MG while unimodal for haplogroup A, and highly significant and negative Fu's Fs values were observed for all MG (-24.06) and haplogroup A (-24.39). Relatively similar patterns of mismatch distribution and significant and negative Fu's Fs values were obtained in previous studies [37,39,42]. More recently, the number of goats in Mongolia has increased fivefold within the last 30 years, more specifically the goat population grew from 5.1 million in 1990 to 27.3 million by 2017 [18].…”
Section: Population Structure and Expansionsupporting
confidence: 78%
See 1 more Smart Citation
“…Currently, the abundant genetic diversity of goats has been assessed by using many different types of molecular markers, including microsatellites (Câmara, Nunes, Diniz, Silva, & Araújo, 2017;E et al, 2018), MHC region variants (Gowane, Akram, Misra, Prakash, & Kumar, 2018), mitochondrial DNA (E et al, 2018;Tarekegn et al, 2018), functional genes (Gowane et al, 2018;Pitarch et al, 2018), and genomewide SNPs (Ilie, Kusza, Sauer, & Gavojdian, 2018;Nicoloso et al, 2015;Onzima et al, 2018). Currently, the abundant genetic diversity of goats has been assessed by using many different types of molecular markers, including microsatellites (Câmara, Nunes, Diniz, Silva, & Araújo, 2017;E et al, 2018), MHC region variants (Gowane, Akram, Misra, Prakash, & Kumar, 2018), mitochondrial DNA (E et al, 2018;Tarekegn et al, 2018), functional genes (Gowane et al, 2018;Pitarch et al, 2018), and genomewide SNPs (Ilie, Kusza, Sauer, & Gavojdian, 2018;Nicoloso et al, 2015;Onzima et al, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Goats (Capra hircus) are economically important domestic animals worldwide. Currently, the abundant genetic diversity of goats has been assessed by using many different types of molecular markers, including microsatellites (Câmara, Nunes, Diniz, Silva, & Araújo, 2017;E et al, 2018), MHC region variants (Gowane, Akram, Misra, Prakash, & Kumar, 2018), mitochondrial DNA (E et al, 2018;Tarekegn et al, 2018), functional genes (Gowane et al, 2018;Pitarch et al, 2018), and genomewide SNPs (Ilie, Kusza, Sauer, & Gavojdian, 2018;Nicoloso et al, 2015;Onzima et al, 2018). The diversity of several indigenous goat breeds in China was assessed Liu et al, 2014;Wang et al, 2017).…”
Section: Backg Rou N Dmentioning
confidence: 99%